Integration Of Unmanned Aerial Vehicle And Multispectral Sensor For Paddy Growth Monitoring Application: A Review - Nur Adibah Mohidem; Suhami Jaafar; Nik Norasma Che’Ya (Universiti Putra Malaysia Press, 2024)
Indexed by WOS/Scopus/ERA